THE NATURE OF HUMAN MISERING IN SURAH AL-MA'ARIJ VERSES 19-21 MAQASHIDI INTERPRETATION APPROACH - Syukri Daud; Hikmatul Hayati; Meinisa Farhani; Bayu Alam Ardiansyah; Syahidatul Nabila (STAI Sebelas April Sumedang, 2025)
This study is entitled